Computational Studies on the Inhibitor Selectivity of Human JAMM Deubiquitinylases Rpn11 and CSN5 - Kumar, Vikash; Naumann, Michael; Stein, Matthias (Frontiers in Chemistry, 2018)
Deubiquitinylases (DUBs) are highly specialized enzymes which are responsible for removal of covalently attached ubiquitin(s) from the targeted proteins. DUBs play an important role in maintaining the protein homeodynamics. Recently, DUBs have emerged as novel therapeutic targets in cancer, inflammation, diabetes and neurodegeneration. Among the different families of DUBs, the metalloprotease group or JAB1/MOV34/MPR1 (JAMMs) proteases are unique in terms of catalytic mechanism. JAMMs exhibit a Zn2+-dependent deubiquitinylase activity. Within the JAMM family, deubiquitinylases Rpn11 and CSN5 are constituents of large bimolecular complexes, namely the 26S proteasome and COP9 signalosome (CSN), respectively. Rpn11 and CSN5 are potential drug targets in cancer and selective inhibitors of both proteins have been reported in the literature. However, the selectivity of JAMM inhibitors (capzimin for RPN11 and CSN5i-3 for CSN5) has not been structurally resolved yet. In the present work, we have explored the binding modes of capzimin and CSN5i-3 and rationalize their selectivity for Rpn11 and CSN5 targets. We found that capzimin interacts with the active site Zn+2 of Rpn11 in a bidentate manner and also interacts with the residues in the distal ubiquitin binding site. MD simulations studies and binding energy analysis revealed that the selective binding of the inhibitors can be only explained by the consideration of larger heterodimeric complexes of Rpn11 (Rpn8-Rpn11) and CSN5 (CSN5-CSN6). Simulation of these protein-protein complexes is necessary to avoid unrealistic large conformational changes. The selective binding of inhibitors is mainly governed by residues in the distal ubiquitin binding site. This study demonstrates that selective inhibitor binding design for Rpn11 and CSN5 JAMM proteases requires consideration of heterodimeric protein-protein target structures.